STRATEGI PENANGANAN PEMBIAYAAN BERMASALAH PADA BAITUL MAAL WAT TAMWIL (BMT) - Sultoni, Hasan (LIPI, 2018)
Abstract Bait al Maal wa Bait al Tamwil (BMT) is a microfinance institution economic social-oriented main activities accommodate religious treasures and channel it for the purpose of realizing the benefit of the people and the nation in the sense that an area ? the breadth. In the treasures of funneling certainly has a lot of problems that one of them is financing bogged down. BMT has a way to minimise the standstill with financing systems family that was drafted in following such a construction, Bank, billing and rescue.   Keywords: handling of problematic financing, baitul maal wat tamwil